Hospital Management Strategies: Impacts on Quality of Care and Patient Satisfaction – A Systematic Review - Ade Rudiono Tria; Puput Indriani; Purwadhi Purwadhi; Yani Restiani Widjadja (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Hospital management strategies, including process optimization, strategic planning, and Total Quality Management (TQM), have demonstrated positive effects on healthcare quality and patient satisfaction. Significant improvements have been observed in specific areas such as administrative efficiency and pharmacy waiting times following Failure Mode and Effects Analysis (FMEA)-based interventions. Patient-centered approaches and TQM consistently enhance service quality dimensions, including reliability, responsiveness, empathy, and assurance. Many studies indicate positive relationships between management strategies and quality indicators, particularly in structural and clinical outcomes, although the connection with patient satisfaction is sometimes inconsistent. These findings highlight the important role of leadership involvement, effective decision-making, and technology integration in improving hospital performance. Evidence also shows that strategic planning contributes to increased patient retention and reduced service complaints in healthcare facilities. This review addresses an important gap by synthesizing recent evidence from both Indonesian and global hospital settings, particularly where resource limitations and health policy factors influence service outcomes. Additional findings reveal stronger patient satisfaction in outpatient and emergency services through empathy-focused staff training and digital health systems. The implications emphasize the need for adaptive and sustainable management strategies, while future research should explore stronger causal relationships between management interventions and patient satisfaction outcomes.